Atlantoaxial Instability in Neurofibromatosis Type 1: A Case Report - Sankalp Lal; Pankaj Kumar Damor; Mahendra Singh Tak; Mukesh Kumar Saini; Mahesh Bhati (Journal of Orthopaedic Case Reports)
Introduction: Neurofibromatosis (NF) is a cluster of conditions in which tumors grow in the nervous system. Even though the spine is the most common site of skeletal involvement in NF type 1 (NF-1), cervical spinal anomalies are infrequent. Case Report: The atlantoaxial joint is a critical transitional zone in the cervical spine and is prone to instability. We report the case of a 49-year-old gentleman with atlantoaxial instability due to NF-1 who presented with quadriparesis and was managed by reduction with skull traction followed by C1-C2 Goel-Harms fixation. Conclusion: In the present case, there was substantial bleeding and significant vertebral dysplasia, which makes the case distinctly unique. Skull traction and C1-C2 Goel-Harms fixation with fusion should be considered for patients with NF-1 complicated by atlantoaxial instability.